2021
DOI: 10.1039/d0ta11457j
|View full text |Cite
|
Sign up to set email alerts
|

Dual active sites fabricated through atomic layer deposition of TiO2 on MoS2 nanosheet arrays for highly efficient electroreduction of CO2 to ethanol

Abstract: Electrochemical reduction of CO2 to ethanol through renewable electricity is highly desirable but still challenging. Here, we demonstrated that TiO2/MoS2 nanosheet arrays synthesized through atomic layer deposition (ALD) of TiO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Since there is no CH x in the electroreduction products, but a certain amount of CO is present, it is suggested that the formation of ethanol probably goes through a CO−CO coupling reaction process. The possible formation process of ethanol is as follows: CO 2 →*CO 2 →*COOH→*CO→*CO+*CO→*OCCO→*OCCHO→*COHCHO→*CCHO→*CHCHO→*CH 2 CHO→*CH 2 CHOH→*CH 3 CHOH→*CH 3 CH 2 OH [38] …”
Section: Resultsmentioning
confidence: 99%
“…Since there is no CH x in the electroreduction products, but a certain amount of CO is present, it is suggested that the formation of ethanol probably goes through a CO−CO coupling reaction process. The possible formation process of ethanol is as follows: CO 2 →*CO 2 →*COOH→*CO→*CO+*CO→*OCCO→*OCCHO→*COHCHO→*CCHO→*CHCHO→*CH 2 CHO→*CH 2 CHOH→*CH 3 CHOH→*CH 3 CH 2 OH [38] …”
Section: Resultsmentioning
confidence: 99%
“…in CO 2 RR due to the synergistic effect of the multiple active sites, thus improving their tandem reaction efficiency. 161–163…”
Section: Catalytic Application Of Dscsmentioning
confidence: 99%
“…The catalyst also showed robust durability. Qi et al 213 fabricated TiO 2 /MoS 2 nanosheets to convert CO 2 into ethanol. Decorating MoS 2 with TiO 2 did not change the original morphology of the MoS 2 material but resulted in more exposed active sites due to the neat distribution of TiO 2 on the surface of MoS 2 .…”
Section: Applications Of Mos2-based Materials In Co2rr Activitymentioning
confidence: 99%